ANALYSIS OF INTEGRATION STRATEGIES IN IMPROVING MARKETING PERFORMANCE STUDY ON FOOD AND BEVERAGE DISTRIBUTORS IN MAKASSAR CITY - Nurul Fadilah Aswar; Hasmyati, Nur Indah Atifah Anwar, Ilham Aksir (BORJUIS: JURNAL OF ECONOMY, 2024)
Increasingly fierce business competition in marketing, companies must work hard to implement various marketing strategies to win the competition. One of the strategies used is to build an integration strategy, where all the company's strengths are synergized to improve marketing performance. This study aims to analyze the factors associated with integration strategies, such as the level of trust, dependencies, and flexibility that have an influence on the company's marketing performance. The study also involved intervening variables, namely flexibility and trust, as a link between these factors and marketing performance. The data analysis method used is Structural Equation Modeling (SEM), with a sample of 100 food and beverage companies in Makassar. The results showed that the level of trust, dependencies, and flexibility significantly affect marketing performance through intervening variables, namely Trust and flexibility. Managerial implications that can be suggested from this study is the importance of building mutually beneficial cooperation between companies, by maintaining a level of trust, flexibility, and the existence of a balanced dependency.